(3QSGdI aj GdeUOQs
(3ChdgG (B:s
(3GYdehG eYGTQ GdWdGH, habce Gddg dfjd GdUhGH Cf GdMOK GdPj Od Ydjg GdeUOQ GdeYdb HZjQg dG eMGdI s
(3BNQgG (B:s
(3hbO Yjf GdhGVY GdefUaI HGdCHjGJ WnqQG Ydi eG aSQg UGMH GdeUGOQ, hgh Cf eYfGg HGdaGQSjI hgPG GdbSe Cbd hLhOkG ef GdHhGbj hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B139 s
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI HGdfLa (B(2/369) s
Keywords: (3GdfMhs